Factors associated with complications during pregnancy - Zeidan, muna (Iraqi National Journal of Nursing Specialties, 2015)
Objective (s): To determine factors associated with the pregnancy complications (Maternal age, education,obstetrical history, gravidity, birth space interval, and smoking).Methodology: A cross-sectional study conducted at Al- washash & Bab-almoadham primary health carecenters. The sample was (non probability convenient sample) which included (550) pregnant women. Thestudy started from 1st April 2014 to 1st of April 2015. The data was collected by direct interview usingspecial questionnaire to obtain socio-demographic information.Results: the result shows that mean age of the subjects was 26.5± 4.39 years, 57.8% were housewives, thesample included 103 premature uterine contractions, 98 pregnancy induced hypertension , 90 urinary tractinfection , and 80 anemic . Analysis of results by logistic regression test shows that (maternal age ,gravidity, gestational age , birth space interval , and smoking ) were significant factors associated withpregnancy complications.Recommendations: health education to all attending pregnant women in MCH centers about risk ofcomplications during pregnancy